Process Improvement of Internal Audit for Airport Ramp Safety - สังข์สุวรรณ วสุ (Journal of Food Health and Bioenvironmental Science, 2016)
Currently, the airline industry has expanded rapidly. As a result, the numbers of passengers who use the service have grown accordingly. Meanwhile, the danger of accidents in aircraft parking area has increased as well. From such information the Department of Civil Aviation has issued a requirement for all airlines to implement safety standards for operation.The results of the audit from the Civil Aviation Department showed that the company of case study has major flaws in its audit process of safety that need to be corrected urgently. This is the reason for the process improvements of this research. The research, entitled Process Improvement of Internal Audit for Airport Ramp Safety, is aimed to serve two objectives 1) to improve the process of internal audits for airport ramp safety according to international aviation safety standard and 2) to verify the process of internal audits for airport ramp safety according to international aviation safety standard. This research reviews the concept of process improvement of internal audit from QC Story by Lueprasitsakun (2002), JSA (1993), JUSE (2001) the process of internal audit by Sopranodorn (2009) and the surveillance requirements of ISO9001 audit and ICAO Ramp Safety Standard applied to the new process. The results have established the new internal audit process consisting of 11 steps. This improved process is comprised of four indicators at the process level and seven indicators at the operational level. The improved process has received consent by the experts and implemented in the real environment for two months. The indicators, as well as the results after implementation, are as follows: 1. The number of internal auditors. This indicator has been set to be at one person in every audit area, which it has never been set beforehand. 2. The percentage of internal audit steps in compliance with the standards. This figure is increased to be 100% after it has never been collected beforehand. 3. The percentage of auditee units audited on scheduled. This indicator is increased 50% to be 100% after the new process implementation. 4. The percentage of all corrective actions resolved by the deadline. It grows up from 70% to 100% after the new process implementation.